One-sided feelings the relationship between some socioemotional factors and parasocial relationship in emerging adults - Canabal, Gellyn D.
The present study examined the relationships between the engagement in parasocial relationships and some socio-emotional factors, including attachment anxiety, need to belong, loneliness, and close relationship satisfaction in emerging adults. A descriptive correlational design with two comparison groups was employed. There were forty respondents (N=40) who were assigned to one of the two groups: with PSR (WPSR; n=20) and with no PSR (WNPSR; n=20). The data were gathered online through Google Forms. The results were analyzed using Spearman's Rank correlational statistics. The study found that there were no significant correlations between the four (4) socio-emotional factors and parasocial relationships. The findings did not support the expected relationships between the said variables. The study suggests a need to clarify the relationships by investigating the causality of socio-emotional factors to parasocial relationships. Keywords: parasocial relationships, attachment anxiety, need to belong, loneliness, close relationship satisfaction